Face Lift. Issue 5 (November 2015) - Wan, Dinah; Small, Kevin H.; Barton, Fritz E.
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Identify the essential anatomy of the aging face and its relationship to face-lift surgery. 2. Understand the common operative approaches to the aging face and a historical perspective. 3. Understand and describe the common complications following face lifting and treatment options. Summary: Surgical rejuvenation of the aging face remains one of the most commonly performed plastic surgery procedures. This article reviews the anatomy of the face and its impact on surgical correction. In addition, this review discusses the evolution of various face-lift techniques and the current surgical approach to the aging face. Finally, this article discusses potential postoperative complications after rhytidectomy and management solutions.